Preparation of Fibrinogen-Depleted Human Platelet Lysate to Support Heparin-Free Expansion of Umbilical Cord-Derived Mesenchymal Stem Cells - Li Ting Kee; Yi Ting Lee; Chiew Yong Ng; Muhammad Najib Fathi Hassan; Min Hwei Ng; Zalina Mahmood; Suria Abdul Aziz; Jia Xian Law (Biology, 2023)
Human platelet lysate (hPL) has high levels of fibrinogen and coagulation factors, which can lead to gel and precipitate formation during storage and cell culture. Heparin derived from animals is commonly added to minimize these risks, but cannot completely eliminate them. Thus, this study proposes an alternative method to prepare fibrinogen-depleted hPL (Fd-hPL) that supports heparin-free expansion of mesenchymal stem cells (MSCs). hPL was added to heparin to prepare heparin-hPL (H-hPL), whilst Fd-hPL was prepared by adding calcium salt to hPL to remove the fibrin clot. The concentrations of calcium, fibrinogen, and growth factors in H-hPL and Fd-hPL were compared. The effects of H-hPL and Fd-hPL on umbilical cord-derived MSCs (UC-MSCs) were assessed. The results showed that Fd-hPL possessed a significantly higher calcium concentration and a lower fibrinogen level than H-hPL. The concentrations of BDNF, TGF-β1, and PDGF-BB showed no significant difference between H-hPL and Fd-hPL, but Fd-hPL had a lower VEGF concentration. Fd-hPL retained the characteristics of UC-MSCs, as it did not affect the cell viability, proliferation, multilineage differentiation potential, or surface marker expression. In conclusion, Fd-hPL effectively supported the in vitro expansion of MSCs without compromising their characteristics, positioning it as a potential substitute for FBS in MSC culture.